Water planting plant container - SUN MENG; CHEN XIAOMEI (2018)
The utility model discloses a water planting plant container, include the vessel and set up in the chassis of vessel bottom, the vessel be upper end opening lower extreme confined structure, the bottom of vessel is provided with the outlet, the chassis with vessel threaded connection, the chassis on be provided with can be with the sealed rubber buffer of outlet, the rubber buffer pass through theconnecting seat with chassis rotatable coupling, the vessel in be provided with the cover body that prevents the evaporation of water, the cover body is big for open -top, horn shaped structure thatthe bottom opening is little, and the upper portion of the cover body is provided with a plurality of bleeder vents, in the bottom of the cover body extended to the vessel, the opening part of cover body bottom was provided with the fixed plate that closes bottom opening lid, the fixed plate on be provided with and alternate the hole. The utility model discloses be convenient for change the waterin the container, reduce th